(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to determine: how good the effect of additional employee income (TPP), how the employee’s performance , and how the influence TPP on employee performance partially and simultaneously at the Jeneponto Regency Education and Culture Office. This study was conducted for 2 months, May to July 2020. The sampling technique was carried out using saturated sampling. The results of the validity instrument test showed rcount> rtable which meant valid and reliability was above 0.7 It was reliable. The results of this study indicated a simple linear regression analysis that was above 0.5 it meant reliable, namely Y = a + bX = Y = 15,263 + 0.603 X t test results showed that the TPP variable had a positive effect on employee performance. The results of the F test showed that the independent variables had a positive effect on employee performance where the value of Pvalue was 0.000 <0.05. The coefficient of determination (R2) showed the amount of contribution 0.371 or 37.1% of the TPP, while the remaining 62.9% was the contribution of other factors that were not examined in this study. Keywords: Performance, Employee, Income.